2018
DOI: 10.22302/iribb.jur.mp.v86i2.284
|View full text |Cite
|
Sign up to set email alerts
|

Biostimulasi pertumbuhan vegetatif tanaman tebu (Saccharum officinarum L.) pada fase awal di lahan kering (Biostimulation of vegetative growth of sugarcane (Saccharum officinarum L.) in the initial phase on dry land)

Abstract: The expansion of sugarcane areas as a support to national sugar production has shifted to sub-optimal dry land. In drought stress conditions, early growth of sugarcane usually can inhibite and decrease its productivity. This study aimed to test the efficacy of organic biostimulant in increasing vegetative growth of sugarcane in the dry land. Firstly, seedlings were submerged with biostimulant of Citorin-Rfor overnight. Secondly, the biostimulant application of Citorin-S was carried out by foliar sprayat age1 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 4 publications
(5 reference statements)
0
3
0
1
Order By: Relevance
“…Biostimulants that contain a complex mixture of polysaccharides, micronutrients, and regulatory hormones, can positively influence the process of photosynthesis, cell metabolism, nitrogen, sulfur metabolism, and stress drought response [6]. Wahyuni et al [8] reported that a complete biostimulant (phytohormone, humic acid, and Mycorrhiza) could provide better vegetative growth. The application of biostimulants in agricultural activities has a positive impact on plants.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Biostimulants that contain a complex mixture of polysaccharides, micronutrients, and regulatory hormones, can positively influence the process of photosynthesis, cell metabolism, nitrogen, sulfur metabolism, and stress drought response [6]. Wahyuni et al [8] reported that a complete biostimulant (phytohormone, humic acid, and Mycorrhiza) could provide better vegetative growth. The application of biostimulants in agricultural activities has a positive impact on plants.…”
Section: Resultsmentioning
confidence: 99%
“…Applying organic biostimulants from seaweed has considerably influenced the growth of sugarcane crops. The use of biostimulants with humic acid and Mycorrhiza increased the vegetative growth of sugarcane, such as height, stem diameter, and plant rooting [8].…”
Section: Introductionmentioning
confidence: 99%
“…That indicated that at six MAP, the application of humic acid caused an increase in the growth of sugarcane stem diameter. The previous study reported by Wahyuni et al (2018) demonstrated an increase in the sugarcane height and stem diameter by 23% to 27% by treating a biostimulant consortium based on humic acid and seaweed enriched with mycorrhiza.…”
Section: Effect Of Humic Acid Application On the Growth And Productiv...mentioning
confidence: 86%
“…Keragaan tebu pada 3 BST ditunjukkan pada Gambar 5. Menurut Wahyuni et al (2018), perlakuan aplikasi konsorsium biostimulan berbasis asam humat, Citorin, dan CMA dapat meningkatan tinggi dan diameter batang tebu varietas Bululawang (BL) sebesar 23% hingga 27% pada 107 HST. Kumalawati et al (2021) menambahkan bahwa aplikasi teknologi Sucrosin belum menunjukkan perbedaan peningkatan tinggi tunas yang signifikan pada 4 dan 6 minggu setelah tanam (MST), sementara pada 8 MST berbeda signifikan terhadap kontrol (17,50 cm) yaitu sebesar 39,25 cm.…”
Section: Pengaruh Aplikasi Tiga Jenis Formula Teknologi Sucrosin Terh...unclassified